FACTORS RELATED TO THE SECOND RUBELLA MEASLES IMMUNIZATION IN KONAWE ISLANDS DISTRICT: Second Rubella Measles - Syahid, Abdul; Supodo, Timbul; Sunarsih (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: National coverage of Rubella-Measles immunization in December 2019 was 87.33%. The coverage of Rubella-Measles 2nd immunization in Southeast Sulawesi Province with the lowest achievement was in Konawe Islands Regency. at 26.35%. This study aimed to analyze the factors associated with measles-rubella 2nd immunization in Konawe Islands Regency. Methods: The design of this study is a quantitative study with a comparative study approach, namely a form of research that compares two groups or more of a certain variable. The study population was 1119 children aged 25 to 30 months, while the study sample was 152 children aged 25 to 30 months, and respondents were mothers who had children aged 25 to 30 months who were selected as samples. The sampling technique used simple random sampling. Descriptive data analysis, inferential analysis, and odds ratio with Chi-square statistical tests were used. Result: The results of the study there is a relationship between knowledge (p-value = 0.000; OR = 1.1) with Rubella Measles immunization. Conclusion: There is a knowledge relationship with measles-rubella 2 immunization in Konawe Islands District.